Artificial Intelligence Applied to Digital Marketing in Machine Learning - Mr. M. V. Prabhakaran, Dr. J. Anandhi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Based on the theory that both manual and cognitive tasks can be replaced by Artificial Intelligence, this study explores, using a qualitative research method, the impact of Artificial Intelligence (AI) in Digital Marketing. An analysis of interviews with 15 experts from different industries related to Marketing and AI shows that AI have impact in Marketing processes and the impact will be bigger in the future. The study reinforces that many of the manual and repetitive tasks of a marketer’s life can already be replaced by AI, and the use of machines working together with humans are the key to better marketing results. The challenges and ethical aspects that lead to a slow or non-adoption of AI have been addressed, and one of the major obstacles is that humans aren’t yet confident in technology and, they are not yet ready for this cultural change. Based on these findings, business decision-makers and managers need to prepare their companies and employees for the implementation of AI in Marketing.